Quantitative investigation of mineral impurities of HiPco SWCNT samples: Chemical mechanisms for purification and annealing treatments. (November 2015) - Remy, Emeline; Cahen, Sébastien; Malaman, Bernard; Ghanbaja, Jaafar; Bellouard, Christine; Medjahdi, Ghouti; Desforges, Alexandre; Fontana, Sébastien; Gleize, Jérôme; Vigolo, Brigitte; Hérold, Claire
Abstract: HiPco single-walled carbon nanotube samples contain a non-negligible amount (about 30 wt.%) of metal-based impurities. These impurities are prejudicial to the development of CNT-based applications. In the literature, there is no agreement for their nature and their relative content. Consequently, the standard purification treatments could not be selective enough and they lead to damage the carbon nanotubes. In this work, we have deeply investigated the mineral impurities of a raw HiPco SWCNT sample by means of several techniques. We were able to identify and quantify at least six iron-based phases that coexist in the HiPco SWCNT samples. The raw SWCNTs were submitted to a selective purification treatment involving a high temperature treatment under chlorine. The results show that the efficiency of the metal removal is improved by increasing the temperature of treatment leading to a purification yield of 95.4%, while preserving the structural quality of the SWCNTs. The analysis of the mineral residues in the purified and annealed SWCNT samples allows to propose the chemical mechanisms involved during the chemical treatments.